In Silico Evaluation of rbcL, matK, and psbA-trnH Regions on the Genus Spatholobus (Fabaceae) - Muwaffiq Faza, Ahmad; Khairunnisa Hidaya, Amira; Fatma Yona, Hafidza; Talitha Pangestu, Twistka; Shafala Safa, Muhammad; Suyanto, Eko; Turhadi, Turhadi; Fatchiyah, Fatchiyah (Universitas Negeri Surabaya, 2024)
Spatholobus is a genus that belongs to the Fabaceae that is known to contain various bioactive compounds and distributed across Asia, including Indonesia. However, exploration of Spatholobus in Indonesia is still rare. Therefore, DNA barcoding is used to support the exploration and conservation of Spatholobus in Indonesia. However, there is no universal marker that can be used across all plant species. In addition, there are still few studies related to DNA barcoding within the genus Spatholobus. The purpose of this study was to evaluate the rbcL, matK, and intergenic spacer psbA-trnH regions in silico that can be used as DNA barcodes for the genus Spatholobus. This study began with a sequence search on the NCBI database including the rbcL, matK, and intergenic spacer psbA-trnH genes in the genus Spatholobus and Phaseolus coccineus as the outgroup. Each sequence was then aligned with ClustalW. Then, a phylogenetic tree was constructed using the Maximum-Likelihood (ML) with 1000× bootstrap. As a result, the rbcL, matK, and psbA-trnH regions can be used as markers for DNA barcoding in the genus Spatholobus with different specifications. The rbcL and matK can be used to distinguish Spatholobus at the genus level, while the psbA-trnH can be used to distinguish Spatholobus at the species level.